Deaf and hard of hearing multilingual learners foundations, strategies, and resources - Cannon, Joanna E.; Guardino, Caroline; Paul, Peter V. (Routledge, Taylor & Francis Group, 2022)
"This critical resource provides foundational information and practical strategies for learners who are d/Deaf or hard of hearing (d/Dhh) multilingual learners. These learners come from backgrounds where their home languages differ from the dominant spoken or sign languages of the culture. This book is a one-stop resource for professionals, interventionists, and families, helping them to effectively support the diverse needs of d/Dhh multilingual learners by covering topics such as family engagement, assessment, literacy, multiple disabilities, transition planning, and more. The book provides vignettes of learners from 25 countries, discussion questions, and family-centered infographic briefs that synthesize each chapter. Deaf and Hard of Hearing Multilingual Learners is a groundbreaking step towards better supporting the many languages and cultures d/Dhh students experience in their lifetime through strength-based and linguistically responsive approaches"--